Kann man eine Abkürzung ausweiten? Variationen zu einer Aufgabeaus den Bildungsstandards Mathematik (mathematica didactica, 2005)
The German Educational Standards for mathematics are illustrated in a concrete form by means of appropriate mathematics tasks which require specific mathematical competencies for their solution. One way in which such tasks can be constructed is by systematically varying a given task. In the present article, the example "Shortcut" from the GermanStandards is altered in various ways, including open and realistic task variants, to show howthis may be done.